Clinical researchAssociation of metabolic syndrome with atherothrombotic blood phenotypes in Asian Indian families with premature coronary artery disease - Kanjilal, Saikat; Shanker, Jayashree; Rao, Veena S.; Mukherjee, Manjari; Iyengar, Shamanna S.; Kakkar, Vijay V. (Archives of Medical Science, 2008)
Introduction: Metabolic syndrome (MS) and its co-morbidities including coronary artery disease (CAD) are highly prevalent among Asian Indians and share common risk factors. The aim of this study was to look for an association of atherothrombotic biomarkers with MS among Asian Indian families with premature CAD. Material and methods: MS subjects were identified employing standard and adapted definitions. Lipids were measured on an auto-analyzer while the non-lipid markers were assayed by the ELISA method. Standard and modified MS definitions were applied to 2316 individuals from 531 families. Results: The ATP III criteria identified a significantly larger proportion of people with MS (N=933, P<0.0001) as compared to WHO (N=708) while maximum gain was seen in the modified MS criteria group (MSmod, N=1333), which included a lowered cut-off for waist circumference (WC) and body mass index (BMI) (P=0.0056). Atherothrombotic blood phenotypes, namely TC, TG, Ox-LDL, ApoB100, fibrinogen, FVII.c, PAI-1, IL-6, hsCRP, P-selectin, sICAM and leptin, were significantly elevated, while HDL-c and adiponectin were lower in the MSmod group (P<0.01). All the above phenotypes correlated significantly with WC and BMI but not with waist-hip ratio. Conlusions: In conclusion, an association of the atherothrombotic blood phenotypes with MS indicates the propensity of people with MS to develop CAD, thereby emphasizing the need for early and precise diagnosis of MS among Asian Indians.